FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR DI KABUAPATEN BERAU (STUDI KASUS PADA KANTOR BERSAMA SAMSAT BERAU) - Dandy Ahmad Drajat (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
The purpose of this study is to determine the effect of taxpayer awareness, service quality, and tax sanctions simultaneously on taxpayer compliance in paying two-wheeled motor vehicle tax. This study is a quantitative study, where primary data is obtained from questionnaires distributed to 100 respondents who are sampled using the Accidental Sampling sampling technique. The data analysis tools used are classical assumption tests (normality tests, multicollinearity tests, and heteroscedasticity tests), multiple linear regression analysis, coefficient of determination tests, correlation coefficient tests, hypothesis tests (F tests and t tests). The results of this study conclude that: 1) Taxpayer awareness has a significant partial effect on taxpayer compliance in paying two-wheeled motor vehicle tax. It can be determined that: the t-count value = 2.518 and the t-table value = 1.984 or 2.518 > 1.984 and the sig value 0.013 < 0.05; 2) Service quality does not have a significant partial effect on taxpayer compliance in paying two-wheeled motor vehicle tax. It can be determined that: the t-count value = 1.629 and the t-table value = 1.984 or 1.629 < 1.984 and the sig value 0.107 > 0.05; 3) Tax sanctions have a significant partial effect on taxpayer compliance in paying two-wheeled motor vehicle tax. It can be determined that: the t-value = 2.177 and the t-table value = 1.984 or 2.177 > 1.984 and the sig value 0.032 < 0.05; 4) Taxpayer awareness, service quality and tax sanctions have a positive and significant effect on taxpayer compliance in paying two-wheeled motor vehicle tax. It can be determined that: the f-value = 6.409 and the f-table value = 2.70 or 6.409 > 2.70 and the sig value 0.001 < 0.05. Which means that H4 is accepted simultaneously against taxpayer compliance in paying two-wheeled motor vehicle tax.